The 'Assyrian mill'. A case study on food processing technology and innovation in the Near East during the Neo-Assyrian period (c. 900–600 BC). (2nd January 2022) - Squitieri, Andrea; Bombardieri, Luca
Abstract : Assyrian mills are innovative grinding tools that were introduced during the Neo-Assyrian period ( c . 900–600 BC) in northern Mesopotamia, and which continued to be attested throughout the Neo-Babylonian, Achaemenid and Hellenistic periods. This paper focuses on the Assyrian mills' morphological characteristics and archaeological contexts, as well as their geographic and chronological distributions, in order to cast light on the possible reasons behind their spread and final demise. Despite being characteristic of the Neo-Assyrian period, these devices did not spread uniformly across the Neo-Assyrian Empire. It will be argued, therefore, that their spread should be seen as being mainly connected with agricultural policies implemented by the Assyrians in some areas of their empire. Following the Neo-Assyrian period, the use of Assyrian mills drastically dropped: one of the possible reasons behind their final demise is the introduction of the Olynthus mill, a competitive grinding device which became predominant during the Hellenistic period.